Factors Influence the Adoption of the Islamic Banking System: Customers Perception in Pakistan - Muhammad Masood Mir; Daniyal Iftikhar; Osama Ahsan; Nousheen Abbas Naqvi (ETIKONOMI, 2019)
The purpose of this paper is to analyze customer perceptions of the banking sector after the advent of the Islamic banking system. This research uses structural equation modeling as its analysis tool. The results of the analysis illustrate that the range of customer service and the length of the bank-customer relationship has a positive impact on customer preferences in choosing Islamic banking. This study provides a framework not only for the banking sector but also for other organizations. This study is an effort so that each organizational policy is appropriate to get customer preferences and optimal results in the form of satisfied and loyal customers.JEL Classification: G21, G29